2014
DOI: 10.1002/ldr.2314
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Fractions Controlling Soil Water Repellency in Sandy Soils From the Doñana National Park (Southwestern Spain)

Abstract: The relationship between soil organic matter (SOM) content and organic molecular assemblages (n‐alkane/alkenes pairs and n‐fatty acids) with soil water repellency (WR) in different sieve fractions (1–2, 0·25–1, 0·05–0·5 and <0·05 mm) was studied in sandy soils from the Doñana National Park (SW Spain) under four vegetation species: Quercus suber (QS), Pteridium aquilinum (PA), Pinus pinea (PP) and Halimium halimifolium (HH). The severity of soil WR [assessed according to the water drop penetration time (WDPT) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 125 publications
(151 reference statements)
5
34
1
Order By: Relevance
“…However, SWR intensity (EPT) in the topsoil that developed under pinewood was severe and significantly higher than under beech cover, which showed slight intensity. Similar results were reported by Butzen et al [31], who pointed out that soils developed under coniferous species are generally more water-repellent than those below broadleaf forests and could be due to, among other factors, the higher lipid content [32], as was observed in the Moncayo Natural Park pine litter [33].…”
Section: Soil Physical Propertiessupporting
confidence: 86%
“…However, SWR intensity (EPT) in the topsoil that developed under pinewood was severe and significantly higher than under beech cover, which showed slight intensity. Similar results were reported by Butzen et al [31], who pointed out that soils developed under coniferous species are generally more water-repellent than those below broadleaf forests and could be due to, among other factors, the higher lipid content [32], as was observed in the Moncayo Natural Park pine litter [33].…”
Section: Soil Physical Propertiessupporting
confidence: 86%
“…Although some intrinsic factors such as soil pH, texture, and nature and content of organic matter influence SWR occurrence and severity (Mataix-Solera & Doerr, 2004;Doerr et al, 2006;Mataix-Solera et al, 2007;Rodríguez-Alleres et al, 2007;Zavala et al, 2009;Jiménez-Morillo et al, 2014), some authors have shown that soil moisture content and temperature are two major abiotic factors affecting dynamics in water repellency Goebel et al, 2011;Hewelke et al, 2014 ). Thus, several studies have revealed a seasonal variation of SWR with high levels in summer and low levels in winter (Crockford et al, 1991;Buczko et al, 2005;Leighton-Boyce et al, 2005;Keizer et al 2007Keizer et al , 2008Hardie et al, 2012;Santos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez‐Morillo et al . () studied soil WR under different vegetation types in an area in southwestern Spain and found more severe WR in soils below oaks than below pines or other species. They attributed this to higher organic matter contents and a high degree of evolution of organic matter, mainly in organic films coating the finer particles.…”
Section: Discussionmentioning
confidence: 90%